Effect of structured rehabilitation versus non-structured rehabilitation following non-surgical management of displaced proximal humerus fractures: a protocol for a randomised clinical trial. Issue 10 (17th October 2022) - Liaghat, Behnam; Brorson, Stig
Abstract : Introduction: An increasing number of patients with displaced proximal humerus fractures (PHF) are being offered non-surgical treatment, including short immobilisation and structured rehabilitation. There are no randomised controlled trials (RCTs) comparing structured rehabilitation with non-structured rehabilitation to investigate the benefits of structured rehabilitation. Methods and analysis: In this RCT, patients with a displaced PHF will be assessed for eligibility at a Danish university outpatient clinic. Patients with competing injuries or patients offered surgery will be excluded, and randomisation will be 1:1. All patients will receive standard orthopaedic follow-up, including 14-day postinjury immobilisation, and advice about returning to activities of daily living before being allocated to structured rehabilitation in the municipalities or non-structured rehabilitation. The primary outcome is the between-group difference in the Oxford Shoulder Score (0–48 points, 48=best, minimal clinically important difference=10) at 6 months. A sample size of 60 patients will allow us to show a 10-point difference with 80% power. Ethics and dissemination: Funded by Department of Orthopaedics, Zealand University Hospital (grant number N/A) and Region Zealand Health Science Research Foundation (R32-A1108-B14), 14 January 2022; The Ethics committee in Region Zealand approved (EMN-2022-02449), 8 April 2022. The site opened on 5 May 2022, and the final results will be updated on trial registries, submitted to a peer-reviewed journal, and inform rehabilitation strategies after displaced PHFs. Protocol version 1, 21 April 2022. Trial registration number: NCT05302089 .